Progressive GAA.TTC repeat expansion in human cell lines. - Scott Ditch (PLoS Genetics, 2009)
Trinucleotide repeat expansion is the genetic basis for a sizeable group of inherited neurological and neuromuscular disorders. Friedreich ataxia (FRDA) is a relentlessly progressive neurodegenerative disorder caused by GAA.TTC repeat expansion in the first intron of the FXN gene. The expanded repeat reduces FXN mRNA expression and the length of the repeat tract is proportional to disease severity. Somatic expansion of the GAA.TTC repeat sequence in disease-relevant tissues is thought to contribute to the progression of disease severity during patient aging. Previous models of GAA.TTC instability have not been able to produce substantial levels of expansion within an experimentally useful time frame, which has limited our understanding of the molecular basis for this expansion. Here, we present a novel model for studying GAA.TTC expansion in human cells. In our model system, uninterrupted GAA.TTC repeat sequences display high levels of genomic instability, with an overall tendency towards progressive expansion. Using this model, we characterize the relationship between repeat length and expansion. We identify the interval between 88 and 176 repeats as being an important length threshold where expansion rates dramatically increase. We show that expansion levels are affected by both the purity and orientation of the repeat tract within the genomic context. We further demonstrate that GAA.TTC expansion in our model is independent of cell division. Using unique reporter constructs, we identify transcription through the repeat tract as a major contributor to GAA.TTC expansion. Our findings provide novel insight into the mechanisms responsible for GAA.TTC expansion in human cells.